1988
DOI: 10.1111/j.1745-6606.1988.tb00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Behavior Characteristics of Older Consumers

Abstract: The marketing and consumer-behavior literature for older consumers is analyzed not only for findings, but also in terms of methodology and scope. Based upon this analysis, determinant market behavior of the elderly is identified, an age standard for describing the older market is proposed, areas for future research are suggested, and a meta analysis of pertinent research is conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
4

Year Published

1993
1993
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 29 publications
2
57
0
4
Order By: Relevance
“…Six garment and four service features were indicated to be important and confirmed findings from the qualitative stage that the range of sizes, returns policy, the fit and size of garments, the employment of helpful and knowledgable staff as well as the style of the garments were issues that the retailer could improve since these posed problems to consumers (Table 9). Findings also confirmed that mature consumers are not only worried about their self-image (Hite and Bellizzi, 1985;Thompson and Chen, 1998), but are also service-oriented (Behling, 1999;Leventhal, 1997;Tongren, 1988) and influenced by how a product is sold to them (Goodwin and McElwee, 1999).…”
Section: Quantitative Phasesupporting
confidence: 64%
See 3 more Smart Citations
“…Six garment and four service features were indicated to be important and confirmed findings from the qualitative stage that the range of sizes, returns policy, the fit and size of garments, the employment of helpful and knowledgable staff as well as the style of the garments were issues that the retailer could improve since these posed problems to consumers (Table 9). Findings also confirmed that mature consumers are not only worried about their self-image (Hite and Bellizzi, 1985;Thompson and Chen, 1998), but are also service-oriented (Behling, 1999;Leventhal, 1997;Tongren, 1988) and influenced by how a product is sold to them (Goodwin and McElwee, 1999).…”
Section: Quantitative Phasesupporting
confidence: 64%
“…Their time is precious, they have the self-assurance to demand proper service and now wish to influence the style of fashion clothing. Previous studies have found that mature women continue to be fashion conscious (Tongren, 1988), still see themselves in the same light as they did when they were young and want to keep looking and feeling good (Behling, 1999;Ostroff, 1989). These findings were confirmed by this study.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…As age increases, dependence on the mass media as an information source also increases, as does the perceived credibility of these messages (Tongren, 1988). The much-cited life-style survey of approximately 4,000 adults reported by Needham et al (1981) found that age is positively associated with newspaper readership; however, there is some indication that the elderly are moving away from newspapers to television and A.M. radio as their primary information sources (Tongren, 1988).…”
Section: Access To I~rmationmentioning
confidence: 97%